Making Connections for Our Changing Mountains: Future Directions for the Mountain Research Initiative (MRI) - Adler, Carolina (2020)
The Mountain Research Initiative (MRI) promotes basic and applied research to understand how drivers and processes of global change present challenges and opportunities in mountain social-ecological systems. It convenes a global network that collectively generates and synthesizes knowledge on global change in mountains that also supports decisions and actions to enable sustainable development. Building on the considerable social and intellectual wealth fostered by the MRI over its past 20-plus years of existence, we outline future directions aimed at supporting and further developing the network as well as our flagship and community-led activities aimed at linking and scaling interdisciplinary and transdisciplinary research efforts within and across mountain regions worldwide.